Reconstruction of past heavy metal concentration in the sediment using the seagrass Enhalus Acoroides (L.F.) royle as a biological indicator - Quebral, Ricardo Diaz (2001)
Bioindicators of heavy metals often describe the recent changes in concentration levels in the marine environment rather than the past metal concentration profile. A correlational study was conducted to test the possibility of reconstructing the historical profile of heavy metal concentration in the sediment by analyzing metals absorbed by the seagrass Enhalus acoroides. Copper, cadmium, lead, and zinc which accumulated in annual sections of the rhizomes and dead leaf fibers of the seagrass were correlated with the concentration levels in the sediment for the corresponding years.
The copper levels in the sediments and in the two seagrass parts were found to be significantly correlated across the seven-year period with R2 values of 66% for sediment vs. rhizome and 32% for sediment vs. dead leaf fiber. Significant but very low correlation was found for zinc (R2 sediment-rhizome: 8% R2 sediment-dead leaf fiber: 11%). No significant correlation was found between seagrass and sediment for lead. It was concluded that Enhalus acoroides is a potential bioindicator in the reconstruction of past copper concentration in the sediment. However, further studies must be conducted to improve the correlation of copper between seagrass and sediment by considering other environmental factors that may have an effect on metal uptake of seagrass.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Heavy metals -- Sampling; Seagrasses -- Effect of heavy metals on; Marine sediments